Advances in Synthesis and Applications of Self-Healing Hydrogels - Fan, Leqi; Ge, Xuemei; Qian, Yebin; Wei, Minyan; Zhang, Zirui; Yuan, Wei-En; Ouyang, Yuanming (Frontiers in Bioengineering and Biotechnology, 2020)
Background: Hydrogels, a kind of three-dimensional (3-D) cross-linked polymer networks with higher water concentration, are receiving more and more attention in the recent years. Self-healing hydrogels, which can return to their original structure and function after physical damage, are especially attractive. Some self-healable hydrogels have several kinds of properties such as injectability, adhesiveness, conductivity, etc., which enable them to be used in the manufacture of drug/cell delivery vehicles, glues, electronic devices and so on. Main body: This review will focus on the self-healing hydrogel synthesis and applications s. Their repair mechanisms and potential applications in pharmaceutical, biomedical and others will be introduced. Conclusions: Self-healing hydrogels are used in various fields because of their ability to recover. Nowadays, new designs such as self-healing double-network (DN) hydrogels are developed to overcome the limitations of other soft materials, providing them with better mechanical properties. The prospect of self-healing hydrogels is promising and they may be further developed for more various applications.